Existence and uniqueness of the global solution to the Navier-Stokes equations - Ramm, Alexander G. (Elsevier, 2015)
A proof is given of the global existence and uniqueness of a weak solution to Navier–Stokes equations in unbounded exterior domains.
Keywords: Global existence; Uniqueness of the weak solution to Navier–Stokes equations